Den tingene iboende kraft - Bloch Ravn, Thomas (Den Gamle By: Danmarks Købstadmuseum (Årbog), 2024)
Med udgangen af marts 2024 slutter Thomas Bloch Ravn som direktør efter godt 28 år i spidsen for Den Gamle By. I disse næsten tre årtier er Den Gamle By blevet gennemgribende gentænkt, og i denne artikel fortæller Thomas Bloch Ravn, hvordan han i sine første år som direktør fik en helt særlig kontakt til Den Gamle Bys oprindelige idé og bankende hjerte. English abstract The Unique Energy At the end of March 2024, Thomas Bloch Ravn will step down as director after 28 years at the helm of Den Gamle By. For nearly three decades, Den Gamle By has undergone an extensive reinvention, and in the article, Thomas Bloch Ravn shares how he has drawn inspiration from founder Peter Holm’s initial plans for his museum. Thomas Bloch Ravn’s connection to this, the essence of Den Gamle By, was forged through conversations with former museum curator Erna Lorenzen, who worked with Peter Holm from 1935 to 1945. The director advises his successor to embrace the unique energy residing deep within Den Gamle By’s core concept.